Meshal Haqadmoni : a Parallel Hebrew-English Text. - Loewe, Raphael (Littman Library of Jewish Civilization, The, 2004)
The intellectual and social universe of thirteenth-century Spanish Jewry seen through Hebrew moralistic animal fables translated into English as rhymed couplets. Fully annotated and illustrated.